2016
DOI: 10.1021/acs.nanolett.5b04157
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Photoresponse of CH3NH3PbI3 Hybrid Perovskite Thin Films at the Nanoscale

Abstract: Perovskite solar cells (PSCs) based on thin films of organolead trihalide perovskites (OTPs) hold unprecedented promise for low-cost, high-efficiency photovoltaics (PVs) of the future. While PV performance parameters of PSCs, such as short circuit current, open circuit voltage, and maximum power, are always measured at the macroscopic scale, it is necessary to probe such photoresponses at the nanoscale to gain key insights into the fundamental PV mechanisms and their localized dependence on the OTP thin-film m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 51 publications
5
151
0
Order By: Relevance
“…Other conductive AFM studies have found that grain boundaries can show both higher or lower short circuit current under illumination, irrespective of the surrounding topography. [55] This indicates that the grain boundaries' properties are likely to be more complex than initially believed, and identifying and controlling grain boundaries that make positive rather than negative contributions to the solar cell's performance will be a key factor in continuous investigations. Similarly, excess PbI 2 has also been added to the precursor solution, leading to improved film formation, with larger grains and fewer pinholes, and thus to improved solar cell performance.…”
Section: Grain Boundaries Passivation and Ion Migrationmentioning
confidence: 99%
“…Other conductive AFM studies have found that grain boundaries can show both higher or lower short circuit current under illumination, irrespective of the surrounding topography. [55] This indicates that the grain boundaries' properties are likely to be more complex than initially believed, and identifying and controlling grain boundaries that make positive rather than negative contributions to the solar cell's performance will be a key factor in continuous investigations. Similarly, excess PbI 2 has also been added to the precursor solution, leading to improved film formation, with larger grains and fewer pinholes, and thus to improved solar cell performance.…”
Section: Grain Boundaries Passivation and Ion Migrationmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Perovskite materials are low cost, and their reasonable ionization energy is comparable to that of conventional hole-injection materials for LEDs. [18,[28][29][30][31] According to the latest reports, [32,33] the external quantum efficiency (EQE) of perovskite LEDs surpassed 20%. In addition, a lot of attention focused on conventional LED materials has switched to the perovskites owing to their sharp band edges, outstanding PL properties, and bright electroluminescence (EL) at room temperature.…”
mentioning
confidence: 99%
“…As one of the characteristic signs of sample deterioration is reduced surface stability that results in surface damage during subsequent scanning, this precludes imaging the evolution of sample deterioration through subsequent scans over the same area. 17,25 …”
mentioning
confidence: 99%